Continuous epileptic negative myoclonus as the first seizure type in atypical benign epilepsy with centrotemporal spikes. Issue 44 (30th October 2020) - Yang, Li; Su, Quanping; Xu, Na; Xu, Liyun; Zhao, Juan; Fan, Chao; Li, Yufen; Li, Baomin
Abstract : Abstract: To figure out which diagnosis is more suitable and which antiepileptic drugs are more sensitive to epileptic negative myoclonus (ENM) as the first seizure type in atypical benign epilepsy with centrotemporal spikes. We reviewed the electroencephalogram (EEG) database of Linyi People's Hospital Affiliated to Shandong University and medical records of patients with ENM onset. The characteristics of epileptic seizures, onset age, treatment process, growth and development history, past disease history, family history, degree of mental deterioration, cranial imaging, and video-EEG were studied retrospectively and followed up. There were 4 cases with ENM onset and 1 with continuous ENM, 3 males and 1 female. The onset age was from 2 years 3 months to 8 years 7 months. The cranial magnetic resonance imaging (MRI) and developmental quotient, as well as the family, personal, and past disease history, were normal. Frequent falls and drops were the main clinical manifestations. Five months after the onset of ENM, case 1 had focal seizures in sleep. ENM was the first and only manifestation in all the other 3 children. Discharges of interictal EEG were in bilateral rolandic areas, especially in midline areas (Cz, Pz), electrical status epilepticus in sleep was found in 3 cases. One child was sensitive to levetiracetam, the other 3 were sensitive to clonazepam. ENM can affect the upper or lower extremities. ENM as the first or only symptom was a special phenomenon in benign epilepsy with centrotemporal spikes (BECTS) variants. Ignorance of midline spikes mainly in Cz or Pz in BECTS might lead to missed diagnosis of ENM. Whether benzodiazepines are viable as a choice of BECTS variants with electrical status epilepticus in sleep when ENM is the first symptom still needs a large sample evidence-based observation.